Contrapuntos de Madrid: desarrollismo y polémica en el documental institucional de interés turístico durante el boom - Rodríguez García de Herreros, Lucía (L'Atalante. Revista de estudios cinematográficos, 2023)
In the 1950s, the General Directorate of Tourism began systematically using short documentaries for tourist promotion purposes. The image of Madrid in these films soon left behind the traditional nativist stereotypes of Spain characteristic of the first half of the decade to embrace the icons, discourses and notions of developmentalism, as was the case in Spanish fiction films. This article analyses the first two documentaries about the Spanish capital that were widely used by the tourist authorities, Contrapunto de Madrid (José López Clemente, 1957) and Sobre Madrid (Jorge Grau, 1960) with the aim of identifying the official stance in relation to this change (promoters, beneficiaries, opponents, etc.). In addition to a discursive analysis of the films, the article presents a pragmatic study of the documentaries, considering how they were used and the reasons for their production, as well as a contextual analysis, which seeks to explain the terms of the controversy that led to the withdrawal of more traditional iconographies and discourses of Madrid in tourism promotion.